Text to speech synthesis for Bangla language - Adnan, Morshed Jaman; Quraishi, Abir Al; Rahman, Arifur (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.